Design of A Security System with Mobile Notifications in Case of Intrusion - Yanogo Kiswendsida Jean Hermann; Gerald Yirga; Nabolle Rachid Gaetan; Kabore Baowendnere Tanguy (Journal of Information System and Informatics, 2023)
Physical security is a crucial aspect of cybersecurity, considering the constant risk of unauthorized intrusions and data theft that companies face. While conventional security measures like alarm systems and video surveillance aim to protect physical infrastructure, they often fall short of meeting businesses' actual requirements. It is vital for companies to have immediate awareness of intrusions and the ability to respond promptly. To tackle this challenge, the recommended approach involves implementing an alert security system that offers real-time notifications. This method entails deploying an Internet of Things (IoT) system equipped with sensors throughout the company's premises. These sensors are specifically designed to detect unauthorized entry, triggering instant alerts to the appropriate personnel via a dedicated mobile application. This application enables seamless communication with the IoT system, enabling swift decision-making in response to potential security breaches. In this research, the initial emphasis was on designing the system using Unified Modeling Language (UML) diagrams. Subsequently, the IoT system was implemented, integrating the necessary sensors. Additionally, a user-friendly application was developed to establish a secure connection between the company's system and employees' mobile devices. Through extensive research efforts, an effective and functional system capable of effectively safeguarding businesses has been successfully devised.